The Influence of Digital Marketing, Brand Trust, and Brand Image on Purchase Decision of Somethinc Copy Paste Breathable Cushion Products - Adya Fitrianne Annisa; Evan Jaelani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of digital marketing, brand trust, and brand image on the purchase decision of Somethinc Copy Paste Breathable Cushion products in Cimahi City. In the digital era, marketing strategies have undergone significant changes, with digital marketing playing an essential role in attracting consumer attention. The study identifies how digital marketing, through social media, e-commerce, and other digital platforms, influences consumer behavior, while brand trust and brand image further affect consumer decisions. A descriptive and causal quantitative approach was used, with data collected through a survey involving 183 respondents. Multiple linear regression analysis was applied to test the impact of the variables. The results show that digital marketing, brand trust, and brand image have a significant positive impact on purchase decisions. Digital marketing enhances brand awareness and consumer engagement, while brand trust provides security and confidence, and brand image shapes perceptions of exclusivity. These findings suggest that integrating digital marketing, brand trust, and brand image in marketing strategies is crucial for increasing purchase decisions and fostering brand loyalty. Further research could explore how these factors interact across other industries and their impact on long-term consumer loyalty and repeat purchases.